Analisis Peningkatan Kualitas Produk Beton Precast Menggunakan Metode Importance Performance Analysis di CV. XYZ - Rahman, Muhammad Ainur; Sulistyowati, Enik; Baladraf , Thabed Tholib (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The precast concrete industry plays a crucial role in construction, but construction companies often face challenges related to inconsistent product quality, resulting in a gap between customer expectations and actual performance. This study aims to analyze the quality attributes of precast concrete products from the customer's perspective and map improvement priorities using the Importance Performance Analysis (IPA) method. This study employs a descriptive quantitative approach using a survey method targeting 35 active customers selected through purposive sampling. The IPA analysis results indicate that surface visual quality is the top priority for improvement, as it falls within Quadrant I. This attribute is considered highly important by customers but its performance remains below expectations. Meanwhile, fundamental attributes such as material strength and dimensional accuracy have demonstrated good performance and should be maintained. Strategic recommendations for the company are to focus resource allocation on improving processes that influence product visual quality to significantly enhance customer satisfaction and trust.